Burnout and emotional intelligence in academic insecurity among Buddhist students in Bandar Lampung - Dila Nofalia; Susanto Susanto; Komang Sutawan (Universitas Sebelas Maret, 2025)
Buddhist students in Bandar Lampung face academic pressure that can trigger burnout and insecurity about their academic abilities. This study aims to determine the significant influence between burnout and emotional intelligence on academic insecurity among Buddhist students in Bandar Lampung. This study uses a survey method with a quantitative approach. The data collection technique uses a questionnaire with a Likert scale. The research population includes 291 students, and the sample is taken using the Solvin formula and the Proportionate Stratified Random Sampling technique. Data analysis was conducted using SPSS (Statistical Package for the Social Sciences) for Windows version 27. The results showed a positive and significant influence between burnout and emotional intelligence on academic insecurity among Buddhist students in Bandar Lampung. In this study, burnout influenced academic insecurity. Emotional intelligence also influenced academic insecurity. Simultaneously, burnout and emotional intelligence together influenced academic insecurity. Thus, the higher the level of Burnout, the higher the level of Academic Insecurity experienced by Buddhist students in Bandar Lampung. The findings indicate the importance of strengthening emotional aspects and the need to develop emotional intelligence-based guidance and counseling programs as well as stress management training on campus. These can be used as preventive strategies against the negative effects of Burnout, especially in the context of Buddhist education. The implication of this study is that the influence of Burnout and Emotional Intelligence on Academic Insecurity reinforces the theory that academic fatigue can reduce students' confidence in facing academic demands. Conversely, high Emotional Intelligence has been proven to reduce the level of Academic Insecurity, which is in line with the theory of emotional intelligence which states that an individual's ability to manage emotions can increase resilience to academic pressure.